Neurological manifestations of Erdheim–Chester Disease. Issue 4 (29th March 2020) - Boyd, Louisa C.; O'Brien, Kevin J.; Ozkaya, Neval; Lehky, Tanya; Meoded, Avner; Gochuico, Bernadette R.; Hannah‐Shmouni, Fady; Nath, Avindra; Toro, Camilo; Gahl, William A.; Estrada‐Veras, Juvianee I.; Dave, Rahul H.
Abstract: Objective: To characterize the spectrum of neurologic involvement in Erdheim–Chester Disease (ECD), a treatable inflammatory neoplasm of histiocytes. Methods: Sixty‐two patients with ECD were prospectively enrolled in a natural history study that facilitated collection of clinical, imaging, laboratory, neurophysiologic, and pathologic data. Results: Ninety‐four percent of the patients had neurologic abnormalities on examination or imaging, and 22% had neurologic symptoms as the initial presentation of ECD. The most common neurologic findings were cognitive impairment, peripheral neuropathy, pyramidal tract signs, cranial nerve involvement, and cerebellar ataxia. Imaging revealed atrophy and demyelination along with focal lesions that were located throughout the nervous system, dura, and extra‐axial structures. The BRAF V600E variant correlated with cerebral atrophy. Brain pathology revealed lipid‐laden, phagocytic macrophages (histiocytes) accompanied by demyelination and axonal degeneration. Interpretation: In patients with ECD, neurologic morbidity is common and contributes significantly to disability. Since neurologic symptoms can be the presenting feature of ECD and, given the mean delay in ECD diagnosis is 4.2 years, it is critical that neurologists consider of ECD and other histiocytosis in patients with inflammatory, infectious, or neoplastic‐appearing white matter. Furthermore, given the broad spectrum of neurologic involvement, neurologists have an important role in a team of specialists treating ECD patients.